PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP PERILAKU SOSIAL MAHASISWA - Diana Uswatun Hasanah; Abdullah Idi; Ahmad Syarifuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
The problem in this study is that researchers see there are some students who do not obey or obey all regulations that apply at UIN Raden Fatah Palembang such as: violating the rules of dress, smoking in the campus area, littering and scribbling existing facilities and infrastructure, and said disrespectfully. This attitude reflects bad behavior. The purpose of this study was to determine the effect of Islamic religious education on the social behavior of 2017 PAI UIN Raden Fatah Palembang graduate students. This study uses quantitative descriptive methods while the type of approach used in this study is correlational, which is to find the relationship between the two variables. While the data collection technique is by distributing questionnaires. The questionnaire was distributed to students and the answers were calculated using a percentage formula then processed and explained descriptively and calculated the two variables using the product moment formula. Based on the results of research with known product moment correlation values ​​of 0.91 and consulted with the table